A Confirmatory Factor Analysis for Mental Health of Adolescents in Eastern Region, Thailand - สิริอัตตะกุล, ปริญญา (Thai Interdisciplinary and Sustainability Review, 2019)
The purpose of this research were to confirmatory factor analysis for mental health of adolescents in eastern region, Thailand and to validated construct validity of model for mental health of adolescents in eastern region, Thailand. The variable was mental health, consisted 4 factors; mental state, mental capacity, mental quality, and supporting factors. The sample consisted of 400 adolescents in eastern region, Thailand. The research instrument was the Thai Mental Health Indicator version 2007 (TMHI-version 2007). Data were analyzed by descriptive statistics, Pearson’s product moment correlation coefficient, confirmatory factor analysis. The research results indicated that the factors of mental health of adolescents in eastern region, Thailand consisted 4 factors; mental quality, mental capacity, supporting factors, and mental state respectively. The standardized factor loading were 0.951, 0.780, 0.673, and 0.649 respectively. The model for mental health of adolescents in eastern region, Thailand was consisted with the empirical data provided 2  =2.242, df=1, p=.134, GFI=0.997, AGFI=0.972, RMR=0.516 and RMSEA=0.055.